Abnormal Complex Karyotyping in A Patient Suspected of Acute Myeloblastic Leukemia (AML-M5): A Case Study - Purbosari Purbosari; Usi Sukorini; Rahmat Dani Satria; Tri Ratnaningsih; Setyawati Setyawati (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2022)
Hemophagocytic Lymphohistiocytosis (HLH) is a condition of immune dysregulation characterized by severe organ damage induced by a hyperinflammatory response and uncontrolled T-cell and macrophage activation. Patients with Acute Myeloblastic Leukemia (AML) may be prone to develop HLH. Hemophagocytic lymphohistiocytosis syndrome in AMLpatients with an abnormal complex karyotyping can worsen the patients' prognosis and outcome. A 47-year-old-female presented with prolonged fever, chills, fatigue, weight loss, productive cough, and anemia (blood transfusion (+)). Laboratory findings: hemoglobin 8.5 g/dL, WBC 151.99x103/Î¼L, and platelet count 28x103/Î¼L, peripheral blood 13% blast like cells, 19% promonocytes, 43% atypical (bizarre) monocytes, 25% neutrophils. Levels of CRP>150 mg/L and procalcitonin 82.67 ng/mL, negative HBsAg, and positive IGRA test. Bone marrow morphology showed hypercellularity, decreased thrombopoiesis and erythropoiesis, increased granulopoiesis, macrophages, and hemophagocytosis. Karyotyping results: abnormal karyotypes: 46: XX (9 cells), 44: X (-18), 45: XX (-4), 45: XX (+7, -2, -16), 46: XX (chtb (3), chtb (4), chtb (5), chtb (9), chtb (12), chtb (22)), 46: XX (chtb (5), chtb (7)), 46: XX (chtb (6), chtb (12)), 46: XX (dic 2), 46: XX (chtb (1) (q12), chtb (3) (p21)), 46: XX (chtb (X) (q25) ), 46: XX (der (9), dic (9)), t (9:22)), 46: XX ((+ 21), (-13) chtb (2), p (23), t ( 9:22)). The conclusion was abnormal complex karyotyping. High concentrations of inflammatory cytokines (interleukin-1, interleukin-6, TNF-alpha, and interferon-gamma) secreted by malignant cells and increased phagocytic function of leukemic cells play an important role in the pathogenesis of HLH. Monocytic components (subtypes AML4 and AML5 of the FAB classification) are predisposing factors in cases of AML-related HLH. Cytogenetic abnormalities involving 8p11 and 16p13 are more common in AML-related HLH. Complex genetic abnormalities exacerbate the prognosis of AML, especially in treatment failure. A concluded that was diagnosed with HLH due to AML-M5 with genetic abnormalities of BCR ABL (+), monosomy, trisomy, and multiple chromatid breakage with high mortality. Karyotyping examination is important to determine the prognosis of the disease.